(untitled) (Communications in Mathematical Research, 2021)
The object of this paper is to investigate the three-dimensional electromagnetic scattering problems in a two-layered background medium. These problems have an important application in today’s technology, such as to detect objects that are buried in soil. Here, we model both the exterior impedance problem and the inhomogeneous medium problem in R^3. We establish uniqueness and existence for the solution of the two scattering problems, respectively.